PEDAL Country Snapshot: Madagascar - Resnick, Danielle (International Food Policy Research Institute, 2025)
Large-scale food fortification (LSFF) helps combat micronutrient deficiencies by adding essential vitamins and minerals to staple foods. This PEDAL assessment identifies key priorities for Madagascar by evaluating its political will and implementation capacity for LSFF. For more information about PEDAL and the detailed Madagascar case study, please see PEDAL for Madagascar brief.